Implementasi Manajemen Pembelajaran Pendidikan Agama Islam Berbasis Pendekatan Sistem - Shalahuddin Shalahuddin; Alfina Islamiyatu Khoiriyah; Asmarita Saputri; Rizkiyatul Rizkiyatul; Zahra Zakiyya (Indonesian Journal of Islamic Educational Management, 2025)
This article aims to analyze the implementation of learning management in Islamic Religious Education (PAI) based on a systems approach within the context of digital-era education. The systems approach is considered relevant as it conceptualizes learning as an integrated process encompassing planning, implementation, supervision, and evaluation to achieve holistic Islamic educational goals. This study employs a qualitative descriptive approach through a literature review, drawing on academic books, national and international journal articles, and relevant scholarly documents related to PAI learning management. Data were analyzed using content analysis techniques to identify key patterns, concepts, and principles underlying the application of the systems approach in PAI learning. The findings indicate that systems-based PAI learning management enhances the integration of spiritual objectives, knowledge acquisition, character development, and the utilization of educational technology. However, its implementation remains challenged by limited digital pedagogical competencies among educators and insufficient institutional policy support. These findings suggest that the systems approach has strong potential to improve the effectiveness and sustainability of PAI learning, provided it is supported by strategic planning, teacher capacity building, and adaptive educational policies